2013
DOI: 10.2304/rcie.2013.8.1.87
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Study of American, Chinese, Japanese and Swedish Early Childhood In-service and Pre-Service Teachers' Perspectives of Fathering

Abstract: The purpose of this study was to examine similarities and differences in perspectives of fathering among American, Chinese, Japanese and Swedish in-service and pre-service early childhood teachers. The participants in the quantitative survey consisted of 67 American in-service and 277 preservice teachers, 118 Chinese in-service and 163 pre-service teachers, 325 Japanese in-service and 350 pre-service teachers, and 105 Swedish in-service and 182 pre-service teachers. Randomly selected participants from these na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Pleck (2010) also explains that some men's fatherhood is related to his masculinity. Likewise, Ito and Izumi-Taylor (2013) have found that culture shapes people's views of fathering. Conversely, Japanese fathers were more likely to balance their childrearing practices with their wives by supporting the mothers' work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pleck (2010) also explains that some men's fatherhood is related to his masculinity. Likewise, Ito and Izumi-Taylor (2013) have found that culture shapes people's views of fathering. Conversely, Japanese fathers were more likely to balance their childrearing practices with their wives by supporting the mothers' work.…”
Section: Discussionmentioning
confidence: 99%
“…The first author created the question that resulted from research into the relations about how early childhood teachers view fathering and childrearing in Japan, Sweden and the USA (Ito & Izumi-Taylor, 2013). The first author collected the Japanese data by asking four leaders of parent support groups to participate in this study.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations